Microscope calibration using laser written fluorescence - Corbett, A; Shaw, M; Yacoot, A; Jefferson, A; Schermelleh, L; Wilson, T; Booth, M; Salter, P (Optical Society of America, 2018)
There is currently no widely adopted standard for the optical characterisation of fluorescence microscopes. We used laser written fluorescence to generate two- and threedimensional patterns to deliver a quick and quantitative measure of imaging performance. We report on the use of two laser written patterns to measure the lateral resolution, illumination uniformity, lens distortion and colour plane alignment using confocal and structured illumination fluorescence microscopes.